Epidemiological and clinical features of acute respiratory infections occurring in St. Petersburg during the 2017–2018 and 2018–2019 epidemic seasons - D. A. Guzhov; E. A. Elpaeva; M. A. Egorova; V. A. Eder; I. L. Baranovskya; S. A. Klotchenko; I. I. Tokin; A. V. Vasin (Журнал инфектологии, 2021)
Objective: to analyze the epidemiological and clinical features of acute respiratory infections occurring during the St. Petersburg 2017-2018 and 2018-2019 epidemic seasons.Materials and methods: the study included 457 patients, treated in St. Petersburg clinics from 2017-2019, displaying symptoms of acute respiratory infection (ARI), including evaluation of their clinical histories. Pathogen types were determined by polymerase chain reaction (PCR). Data analysis was carried out using mathematical statistics methods using the Statistica 10 software package (StatSoft Inc.).Results: in this study, we examined the epidemiological and clinical features of acute respiratory infections in St. Petersburg occurring during two epidemic seasons, 2017-2018 and 2018-2019. The 2017-2018 season was characterized by a prevalence of infections caused by influenza B viruses and influenza A subtype H3N2 viruses. In the 2018-2019 season, there was a greater number of acute respiratory viral infections (ARVIs) and infections caused by influenza A subtype H1N1pdm; influenza B virus was detected only in isolated cases. In the 2017-2018 sore throats and muscle aches were a characteristic symptom of influenza A H1N1pdm infections, of bacterial infections – only sore throats. It was shown that throat pain and vasodilation of the scleral and soft palate vessels were significantly more frequent in the 2017-2018 season, compared to the 2018-2019 season. Cough and redness of the posterior pharyngeal wall were hallmark signs of ARVIs in the 2018-2019 season.Conclusion: according to the data, each epidemic season is characterized not only by its own type-specific acute respiratory infection frequencies, but also by different clinical manifestation frequencies. For global monitoring, treatment effectiveness evaluation, and refined study of acute respiratory infection clinical features, it is advisable to use approaches which incorporate accurate, specific, and rapid molecular biological methods capable of identifying a broad range of pathogens.